Environmentally Friendly Production of D(-) Lactic Acid by Sporolactobacillus nakayamae: Investigation of Fermentation Parameters and Fed-Batch Strategies - Michelz Beitel, Susan [UNESP]; Fontes Coelho, Luciana [UNESP]; Sass, Daiane Cristina [UNESP]; Contiero, Jonas [UNESP] (Hindawi, 2017)
The interest in the production of lactic acid has increased due to its wide range of applications. In the present study, the variables that affect fermentative D(-) lactic acid production were investigated: neutralizing agents, pH, temperature, inoculum percentage, agitation, and concentration of the medium components. An experimental design was applied to determine the optimal concentrations of the medium components and fermentation was studied using different feeding strategies. High production (122.41 g/L) and productivity (3.65 g/L·h) were efficiently achieved by Sporolactobacillus nakayamae in 54 h using a multipulse fed-batch technique with an initial medium containing 35 g/L of yeast extract (byproduct of alcohol production), 60 g/L of crystallized sugar, and 7.5 mL/L of salts. The fermentation process was conducted at 35°C and pH 6.0 controlled by NaOH with a 20% volume of inoculum and agitation at 125 rpm. The production of a high optically pure concentration of D(-) lactic acid combined with an environmentally friendly NaOH-based process demonstrates that S. nakayamae is a promising strain for D(-) lactic acid production.